Exploring Genetic Diversity for Yield and Yield Attributing Traits in Pea (Pisum sativum L.) through D² and Principal Component Analysis - Anand, Kumar Jai; Singh, S. K.; Patel, Teena; Nagre, Sachin Prakash; Katara, Vijay Kumar (International Journal of Economic Plants, 2025)
An experiment was conducted during the rabi season of November, 2019–April, 2020 at JNKVV, Jabalpur, Madhya Pradesh (482 004), India to scrutinize the genetic diversity among different Pea genotypes. Using Mahalanobis D2 Statistics, 52 genotypes were grouped into 8 clusters. Cluster I (32 genotypes), cluster II (12 genotypes), and cluster VI (3 genotypes) were found to be poly-genotypic, while the rest of the clusters were mono-genotypic. Notably, the genotypes of cluster II exhibited the highest inter-cluster distance with the genotype of cluster V, indicating significant potential for widening the genetic base of pea. Furthermore, the highest intra-cluster distance was found in cluster VI. Principal Component Analysis demonstrated that five principal components (PCs) exhibited more than 1.00 Eigen value, accounting for approximately 80.62% variability among the traits studied. PC1 demonstrated the highest variability at 36.18%, followed by PC2 (15.55%), PC3 (13.33%), PC4 (8.27%), and PC5 (7.28%). The PC1 loaded with yield traits including plant height, number of nodes plant-1, pod-bearing length, number of pods plant-1, effective pods plant-1, seeds plant-1, biological yield, and seed yield plant-1. The PC2 predominantly represented phenological traits such as days to first flower, days to 50% flowering, and days to maturity. The PC3 encompassed the harvest index, while PC4 focused on 100 seed weight. In contrast, PC5 is linked to pod length and seeds per pod. Additionally, based on PCA, the genotypes FP 14–21, JP 180, VRP 5, AMAN, HVP–2 and FP 14–17 were identified as potential lines.